Answer:
f · g = 24x² - 52x + 24
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Algebra I
- Terms/Coefficients
- Expand by FOIL
- Functions
- Function Notation
Explanation:
Step 1: Define
Identify
f(x) = 4x - 6
g(x) = 6x - 4
Step 2: Find f · g
- Substitute in function values: f · g = (4x - 6)(6x - 4)
- Expand [FOIL]: f · g = 24x² - 16x - 36x + 24
- [Subtraction] Combine like terms: f · g = 24x² - 52x + 24